O espaço tempo virtual : uma análise langeriana do serialismo integral de Pierre Boulez - Oliveira, André Luiz Chitto de (2019)
Pierre Boulez, from the dodecaphonic technique, extended to the others sound properties the formative principles of the series, beginning a strict structural system: the integral serialism. Theodor W. Adorno, in some writings, analyzed the annihilation of the temporal becoming in the boulezian serialist music, and the consequence of the creation of a static music, resulting in the prevalence of a spatial illusion about the musical time. The main purpose of this work is develop an analysis of what is created by integral serialism of Pierre Boulez, using as a basis the Susanne Langer’s philosophical esthetic. The philosopher affirms that the music creates, as a primary illusion the virtual time, and in second order, the virtual space. However, as the adornian analysis, shows that Boulez serial music produce the opposite: the primary illusion is the virtual physical space; the secondary is the virtual time. As a new proposal, it is pertinent the creation of a new one concept, philosophically grounded on Larger’s philosophy, named virtual space-time, which one can be analogically associated with the modern conceptions of space in physics.